Estudo comparativo de indicadores de saúde bucal em modelos assistenciais da Atenção Básica de São Carlos/SP a partir do SIA-SUS - Magri, Laís Valencise (2013)
The planning and evaluation of oral health practices are essential in the context of primary care. In this sense, the oral health indicators are important instruments for quantitative analysis, which can be used with these purposes. The aim of this study was to compare four oral health indicators [Income Indicator (II) Attrition (AI), Modified Prevention Emphasis (MPEI), Indicator Value Restoration / Extraction (IVRE), and the Relationship First Consultation/Urgency (RFCU)] in the Family Health Units (FHU) and Basic Health Units (BHU) in São Carlos/SP, in the period 2008-2011. Study participants were 15 FHU and 11 BHU. The data of the dental procedures performed were extracted from the Outpatient Information System (SIA-SUS) and the indicators were calculated according Narvai (1996). Statistical analysis was performed by Mann- Whitney test, adopting a significance level of 5%. The average (standard deviation) of II, AI, MPEI, IVRE and RFCU during the study period were, respectively, 20 (10.9), 7.5 (17.8), 0.06 (0.24); 5.2 (1.4), 0.7 (0.6) to BHU and 18.2 (12.2), 13.1 (20.1), 0.12 (0.33); 4.7 (2.1), 0.3 (0.5) for the FHU. Significant differences (p <0.05) were observed for IVRE and RFCU. It can be concluded that although BHU have shown a better performance than the FHU in São Carlos, in the period studied, the results also indicated a strengthening process of the Family Health Strategy. MPEI, AI and RFCU showed unsatisfactory results, pointing to the difficulty in implementing prevention and health promotion, difficulty in reaching the target audience and dental care focused on emergency and curative procedures. IVRE and II showed the best results, indicating high productivity in terms of dental care and a model focused on conservative practices.